2008
DOI: 10.1007/s00284-008-9115-y
|View full text |Cite
|
Sign up to set email alerts
|

The shf Gene of a Shigella flexneri Homologue on the Virulent Plasmid pAA2 of Enteroaggregative Escherichia coli 042 Is Required for Firm Biofilm Formation

Abstract: Enteroaggregative Escherichia coli (EAEC) is an increasingly important cause of diarrhea in both developing and industrialized countries, and is characterized by strong biofilm formation on the intestinal mucosa. Sequencing of the virulent plasmid pAA2 of the prototype EAEC 042 revealed a cluster of three open reading frames (ORFs; shf, capU, and virK) ca. 93% identical to a similar cluster located in Shigella flexneri. The function of the first ORF Shf protein is not known, but the closest well-characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
2
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 20 publications
1
27
2
11
Order By: Relevance
“…To date, most studies of EAEC adherence have focused on structural adhesins known as aggregative adherence fimbriae. However, recent research has shown that EAEC strains also harbor an expanding repertoire of nonstructural outer membrane proteins that contribute to colonization (1,4,14,28).One such outer membrane protein is heat-resistant agglutinin 1 (Hra1), an accessory adhesin that we recently characterized in EAEC strain 042 (1). The hra1 gene (along with its 90% identical allelic variant hek, reported from uropathogenic E. coli and neonatal meningitic E. coli [11,39]) is predicted to encode a 29-kDa precursor, which is processed to a 25-kDa outer membrane protein.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, most studies of EAEC adherence have focused on structural adhesins known as aggregative adherence fimbriae. However, recent research has shown that EAEC strains also harbor an expanding repertoire of nonstructural outer membrane proteins that contribute to colonization (1,4,14,28).One such outer membrane protein is heat-resistant agglutinin 1 (Hra1), an accessory adhesin that we recently characterized in EAEC strain 042 (1). The hra1 gene (along with its 90% identical allelic variant hek, reported from uropathogenic E. coli and neonatal meningitic E. coli [11,39]) is predicted to encode a 29-kDa precursor, which is processed to a 25-kDa outer membrane protein.…”
mentioning
confidence: 99%
“…To date, most studies of EAEC adherence have focused on structural adhesins known as aggregative adherence fimbriae. However, recent research has shown that EAEC strains also harbor an expanding repertoire of nonstructural outer membrane proteins that contribute to colonization (1,4,14,28).…”
mentioning
confidence: 99%
“…Other studies suggest that the Shf protein-encoding gene (shf) is required for strong biofilm formation of EAEC serotype O42, and that transcription of the shf gene is dependent on AggR (Fujiyama et al, 2008). There is considerable heterogeneity in putative virulence genes of EAEC isolates from diarrhoeic children in India and biofilm formation appears to be associated with multiple genes (Wani et al, 2012).…”
Section: Biofilm Formation By Eaec 46mentioning
confidence: 99%
“…Tais genes codificam a toxina termoestável EAST-1, a proteína Shf, envolvida na formação de biofilme, o usher da fímbria AAF/III e uma proteína envolvida na biossíntese de yersiniabactina, respectivamente (BERNIER et al, 2003;CZECZULIN et al, 1999;FUJIYAMA et al, 2008;SAVARINO et al, 1993).…”
Section: Análise Da Presença De Outros Genes De Eaecunclassified
“…Monteiro-Neto et al (2003) descreveram uma proteína de 58 kDa (Ap58) que, na amostra 236 do sorotipo O111:H12, apresentava as mesmas funções descritas por Debroy et al (1995). O gene que codifica a Ap58 foi localizado no cromossomo da amostra protótipo (MONTEIRO-NETO et al, 2003).No plasmídeo pAA, também estão localizados os genes aggR, que codifica um regulador de virulência (NATARO et al, 1994), pet, que codifica uma enterotoxina autotransportadora (ESLAVA et al, 1998), shf, envolvido na formação de biofilme em EAEC 042 (FUJIYAMA et al, 2008) e aatA, que codifica uma proteína de membrana externa que faz parte de um complexo transportador de proteínas (NISHI et al, 2003). O fragmento sonda EAEC (CVD432) desenvolvido por Baudry et al (1990), corresponde a uma porção deste último gene.…”
unclassified